Haššātān and Court Traditions in the Book of Job: Court Tradition History Perspective - Agus Santoso; Bobby Kurnia Putrawan; Yusak Tanasyah; Iswahyudi Iswahyudi (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2022)
The book of Job contains about suffering and feelings of injustice. Job felt and asked why he as a godly person experienced suffering, so he sought justice to God. The word justice is related to haššātān and court. The authors want to find and describe the context of the word haššātān by the judicial or court tradition history perspective in the book of Job. The result of this research is that the dialogue and the setting of the dialogue in the sky is the atmosphere of the court which was attended by the Judge (God) and the prosecutor (haššātān), that the prosecutor stated that there was an act of injustice that occurred in the life of the defendant (Job) which was committed by God (as well as the accused), which is also as a discussion of theodicy and Judgment Traditions in the book of Job.